Problems Caused by Word Order when Interpreting / Translating from English into Japanese: The Effect of the Use of Inanimate Subjects in English - Uchiyama, Hiromichi (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1991)
AbstractOne of the most significant difficulties facing an English-Japanese interpreter or translator is the use in English of inanimate subjects which perform intentional acts. While this is a fairly common construction in English, the Japanese normally find it difficult to conceive of an inanimate subject performing a conscious act. English-Japanese interpreter/translators therefore need to be able to interpret such English sentences so that they correspond to the Japanese perception. This paper outlines one method of dealing with this problem - the conversion of the inanimate subjects in the English sentence into an adverbial phrase or clause in Japanese. This serves to reduce the level of difficulty in handling a sentence with a modifying clause the subject of which is inanimate. Practical examples of the use of this method are given. This method also has relevance for interpreter/translator training, as it can be presented to students as a possible means of overcoming a common problem in English-Japanese interpreting and translation.